Social security strategies and redistributive effects in European social transfer systems - Margit Kraus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper evaluates the linkage between social security strategies and redistributive effects in EU social transfer systems. It is argued that the various European systems produce different patterns of redistribution that may be explained by the adoption of different mixes of social security strategies. In support of this argument, several idealtypical strategies are characterized and a classification of European social transfer systems is introduced. Subsequently, the redistributive effects of the systems are assessed and the relationship to their class assignment is investigated. We conclude that the redistributive effects differ markedly between systems of different classes, indicating that redistributive patterns are heavily influenced by the adopted strategy mix.
Keywords: I38; H53; I32; 330; European Social Security Systems; Classification; Redistribution; Soziale Sicherung; Sozialpolitik; Sozialstaat; Einkommensumverteilung; Vergleich; Einkommensverteilung; EU-Staaten